PERANCANGAN MODEL WISATA EDUKASI DI OBJEK WISATA DESA SADE LOMBOK TENGAH - Andi Saputra; Yuliana Pertiwi (Jurnal Pengabdian Masyarakat Berkelanjutan, 2025)
Sade Village in Central Lombok is one of the most famous cultural tourist attractions in Indonesia. The village has great potential to be developed as an educational tourism destination that combines elements of culture, history and local wisdom. The design of an educational tourism model in Sade Village aims to create a meaningful tourism experience for visitors, while preserving culture and improving the welfare of the local community. The model is designed with a participatory approach, involving the local community, government, and relevant stakeholders. Through this model, it is hoped that Sade Village can become an example of sustainable community-based ducational tourism development